Controle de biorreator com base em modelo de fluxos metabólicos : sintonia das condições de microaeração para maximização da produção de etanol por S. cerevisiae - Mesquita, Thiago José Barbosa (2017)
Biofuels are alternatives to fossil fuels, and bioethanol produced from corn and sugarcane is one of the main liquid biofuel currently used. To reach ethanol production maximum yield, it is important to use all fermentable fractions found in cellulosic waste. These fractions are fermented anaerobically, which compromises the final yield of the product of interest, as well as cell viability. In addition, maximizing the conversion of these sugars to ethanol requires the development of a precise control of the dissolved oxygen supplementation to maintain the microaerobic condition. The present work had as objective to increase ethanol yield and productivity by using an innovative control strategy based on the metabolic flows. To implement the proposed control strategy, S. cerevisiae metabolism was simulated, in different glucose and oxygen supply conditions, using the Optflux software and the iND750 genomic scale model reconstructed for Saccharomyces cerevisiae. The combinations of oxygen and substrate fluxes were used to generate mathematical correlations, which were used to manipulate the air, nitrogen and fresh medium feed flows to direct the substrate and oxygen experimental flows to the ethanol production maximization as predicted by the simulations. The control logic was implemented in the SUPERSYS_HCDC program using the LabView 8.0 platform. The five cultivations, about 12 h each, were performed in fed batch mode into a 5 L bioreactor using commercial S. cerevisiae (baking yeast) and glucose as carbon source (30 g.L-1 culture medium and 300 g.L-1 feed medium) in minimal medium (KH2PO4 5,0 g.L-1, MgSO4.7H2O 2,0 g.L-1, Urea 1,5 g.L-1). The cell concentration was monitored during cultivation by optical density measurements (600 nm) and correlated with dry mass measurements. The sugars and metabolites concentration was measured by high-performance liquid chromatography (HPLC), cell viability was monitored by cell counting in Neubauer chamber, after methylene blue coloring. Ethanol yield was 0.48 gethanol. gsubstrate-1 for cultivations submitted to the metabolic fluxes control, which is very close to the theoretical yield (0.51 gethanol. gsubstrate-1). The cultivations conducted without the gas phase supply ("Usina" type) and strictly anaerobic, presented yield of 0.32 gethanol. gsubstrate-1. The closed-loop control strategy favored low cells yields (0.10 gcells. gsubstrate-1) and low glycerol yields (0.056 gglycerol. gsubstrate-1). However, even using the proposed control, the cultures presented a substrate accumulation caused by the natural product (ethanol) inhibition. The proposed control strategy can be extended to other processes, because it may maximize the production of any metabolite that is favored by microaerobic conditions.